Design of Digital-Based SBAR Communication Application in Handover Implementation at Undata Hospital, Central Sulawesi Province - Viere Allanled Siauta; Adillah Imansari; Olivia Ice Lilipaly (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Effective communication could be done by SBAR method, by SBAR communication could be used by health team members while doing handover to other teams. The main communication failure toward nurse is the lack of communication among providers that supports that the handover process is very important in health care. Currently, not all staff nurses know what kind of data should be reported during handover. In answering the problems found, it is necessary to perform digital-based SBAR so as to ensure the completeness of documentation, as well as improve nursing services and patient safety. The purpose of this study was to design a digital-based SBAR communication application in handover implementation at Undata Hospital, Central Sulawesi Province. Methods: The type of research is qualitative research with the research and development method, which is a method used to produce a particular product. Results: Qualitative research to explore the SBAR form as the initial part of designing a web-based management information system in order to increase the effectiveness of communication during the handover process, through data with input, process and output activities in the handover process at Undata General Hospital, Central Sulawesi Province. Conclusion: Nursing services at Undata General Hospital of Central Sulawesi Province require applications in conducting nursing documentation so that handovers between nurses and other health teams could be done effectively. This SBAR communication design is expected to be further developed into an application development that implemented in hospitals.